Models of Disability in Children’s Pretend Play: Measurement of Cognitive Representations and Affective Expression Using the Affect in Play Scale - Federici, Stefano; Meloni, Fabio; Catarinella, Antonio; Mazzeschi, Claudia (Frontiers in Psychology, 2017)
Play is a natural mode of children’s expression and constitutes a fundamental aspect of their life. Cognitive, affective, and social aspects can be assessed through play, considered as a “window” to observe a child’s functioning. According to Russ’s model, cognitive and affective components and their reciprocal connections can be assessed through the Affect in Play Scale (APS). The aim of the present study was to investigate children’s representations of the three main models of disability (medical, social, and biopsychosocial) and how these models affected cognitive and affective components of children’s play. Sixty-three children, aged 6–10 years, were assessed by means of the APS. Participants were randomly assigned to one of two APS task orders: the standard APS task followed by the modified APS task (including a wheelchair toy), or vice versa. The standard and modified APS sessions were coded according to the APS system. The modified APS sessions were also coded for the model of disability expressed by children. A one-way ANOVA conducted on the APS affective and cognitive indexes revealed an effect of condition on the affective components of play and no effect on cognitive components and variety of affect as assessed by the APS. In addition, when children are involved in pretend play from which concepts of disability emerge, these concepts are almost exclusively related to the medical model of disability. Results suggested implications for intervention with children in educational contexts that aim to teach children about disability.